IN SILICO SCREENING OF ANTIMALARIAL FROM INDONESIAN MEDICINAL PLANTS DATABASE TO PLASMEPSIN TARGET - Rifai, Eko Aditya; Hayun, Hayun; Yanuar, Arry (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Malaria is a disease that impacts millions of people annually. Among the enzymes, plasmepsin is the main enzyme in the plasmodium life cycle that degrades hemoglobin during the erythrocytic phase in the food vacuole. Recently, pharmaceutical industries have been trying to develop therapeutic agents that can cure malaria through the discovery of new plasmepsin inhibitor compounds. One of the developing approaches is the in silico method. Methods: The chosen in silico screening method in this experiment is a structure-based screening using GOLD software and the Indonesian medicinal plants database. Results: From ten in silico screening runs, three of the compounds always ranked in the top ten. These three compounds are trimyristin, cyanidin 3,5-di-(6-malonylglucoside), and isoscutellarein 4'-methyl ether 8-(6â€-n-butylglucuronide). Another compound that emerged with high frequency is cyanidin 3,5-di-(6-malonylglucoside). Conclusions: Based on the results obtained from this screening, 11 inhibitor candidates are expected to be developed as antimalarial. These compounds are trimyristin; cyanidin 3,5-di-(6-malonylglucoside); isoscutellarein 4'-methyl ether 8-(6â€-n-butylglucuronide); cyanidin 3-(6â€-malonylglucoside)-5- glucoside; multifloroside; delphinidin 3-(2-rhamnosyl-6-malonylglucoside); delphinidin 3-(6-malonylglucoside)-3',5'-di-(6-p-coumaroylglucoside); cyanidin 3-[6-(6-sinapylglucosyl)-2-xylosylgalactoside; kaempferol 3-glucosyl-(1-3)-rhamnosyl-(1-6)-galactoside; sanggenofuran A; and lycopene with a GOLD score range from 78.4647 to 98.2836. Two of them, Asp34 and Asp214, bind with all residues in the catalytic site of plasmepsin.